2011
DOI: 10.1007/s10464-011-9435-0
|View full text |Cite
|
Sign up to set email alerts
|

The Test of Time in School‐Based Mentoring: The Role of Relationship Duration and Re‐Matching on Academic Outcomes

Abstract: The influence of match length and re-matching on the effectiveness of school-based mentoring was studied in the context of a national, randomized study of 1,139 youth in Big Brothers Big Sisters programs. The sample included youth in grades four through nine from diverse racial and ethnic backgrounds. At the end of the year, youth in intact relationships showed significant academic improvement, while youth in matches that terminated prematurely showed no impact. Those who were re-matched after terminations sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
186
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 40 publications
(59 reference statements)
7
186
0
Order By: Relevance
“…Many factors that affect the chances of developing mentorship relationships are also certain to be associated with employment outcomes (Kammeyer-Mueller and Judge 2008). Research on formal mentoring programs has addressed this problem by implementing experimental designs that randomly assign individuals to either the treatment (mentored) or the control (non-mentored) group (for example, Grossman et al 2012;Tierney et al 1995). This ensures the equivalence of those groups and allows researchers to rule out spuriousness as a potential explanation for mentoring effects.…”
Section: Causal Influence Of Mentoringmentioning
confidence: 99%
“…Many factors that affect the chances of developing mentorship relationships are also certain to be associated with employment outcomes (Kammeyer-Mueller and Judge 2008). Research on formal mentoring programs has addressed this problem by implementing experimental designs that randomly assign individuals to either the treatment (mentored) or the control (non-mentored) group (for example, Grossman et al 2012;Tierney et al 1995). This ensures the equivalence of those groups and allows researchers to rule out spuriousness as a potential explanation for mentoring effects.…”
Section: Causal Influence Of Mentoringmentioning
confidence: 99%
“…Previous research has identified an average length of SBM matches to be about 5 months [20]. Our experience keeping pairs together for at least 1 year is particularly interesting since recent work has suggested that college student mentors may be associated with increased premature relationship termination [11]. We attribute our success to the clear expectations set at the time of mentor recruitment, ongoing mentor support and selection for motivated participants due to the rigorous upfront training requirements.…”
Section: Discussionmentioning
confidence: 86%
“…Several factors are associated with successful relationships, including setting clear visit expectations, focusing on building trust and friendship, recruiting mentors with experience working with children, providing adequate mentor orientation and ongoing training, and facilitating mentors' feelings of effectiveness [2][3][4][5]10]. Relationship length also appears to be a critical component to successful mentoring outcomes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the racial and socioeconomic differences that are common between college student mentors and their youth mentees (Herrera et al, 2007) can result in early relationship termination when these issues are not handled sensitively (Spencer, 2007). Perhaps for these reasons, college student mentors were found to be 46% less likely to have an intact match at the end of a school year compared to other mentors (Grossman, Chan, Schwartz, & Rhodes, 2012).…”
Section: Challenges Of Mentoringmentioning
confidence: 99%